Large Animal Model of Pumpless Arteriovenous Extracorporeal CO2 Removal Using Room Air via Subclavian Vessels. Issue 1 (January 2016) - Witer, Lucas J.; Howard, Ryan A.; Trahanas, John M.; Bryner, Benjamin S.; Alghanem, Fares; Hoffman, Hayley R.; Cornell, Marie S.; Bartlett, Robert H.; Rojas-Peña, Alvaro
Abstract : End-stage lung disease (ESLD) causes progressive hypercapnia and dyspnea and impacts quality of life. Many extracorporeal support (ECS) configurations for CO2 removal resolve symptoms but limit ambulation. An ovine model of pumpless ECS using subclavian vessels was developed to allow for ambulatory support. Vascular grafts were anastomosed to the left subclavian vessels in four healthy sheep. A low-resistance membrane oxygenator was attached in an arteriovenous (AV) configuration. Device function was evaluated in each animal while awake and spontaneously breathing and while mechanically ventilated with hypercapnia induced. Sweep gas (FiO2 = 0.21) to the device was increased from 0 to 15 L/min, and arterial and postdevice blood gases, as well as postdevice air, were sampled. Hemodynamics remained stable with average AV shunt flows of 1.34 ± 0.14 L/min. In awake animals, CO2 removal was 3.4 ± 1.0 ml/kg/min at maximum sweep gas flow. Respiratory rate decreased from 60 ± 25 at baseline to 30 ± 11 breaths per minute. In animals with induced hypercapnia, PaCO2 increased to 73.9 ± 15.1. At maximum sweep gas flow, CO2 removal was 3.4 ± 0.4 ml/kg/min and PaCO2 decreased to 49.1 ± 6.7 mm Hg. Subclavian AV access is effective in lowering PaCO2 and respiratory rate and is potentially an effective ambulatory destination therapy for ESLD patients.